"String art" approach to the design and manufacturing of optimal composite materials and structures. (15th August 2020) - Ostanin, Igor
Abstract: In this paper we report a new promising idea on the design and manufacturing of ply composite structures, tailored to exhibit maximum stiffness under given weight constraints and loading conditions. It is based on the idea behind an artistic technique known as "string art" – the representation of an image with a single thread, tensioned between pins on the flat frame. A discrete optimization algorithm has been employed recently to formalize the process of finding a configuration of thread windings that fuses into a given greyscale image. We demonstrate how this algorithm can be employed to approximate the two-dimensional distribution of isotropic material, computed by a conventional topology optimization algorithm. An optimal composite design is thus found as a result of the following two-stage process. At the first stage, topology optimization procedure produces regular grid of greyscale values of stiffness. At the second stage, this distribution is approximated with a polyline, representing the stiff reinforcement fiber in a soft matrix, according to "string art" optimization algorithm. The efficiency of the proposed approach is illustrated with few simple numerical examples. Our development opens a wide avenue for the industrial design of the new generation of fibrous composite structures.